Fractalkine Attenuates Microglial Cell Activation Induced by Prenatal Stress. (27th April 2016) - Ślusarczyk, Joanna; Trojan, Ewa; Głombik, Katarzyna; Chamera, Katarzyna; Roman, Adam; Budziszewska, Bogusława; Basta-Kaim, Agnieszka
Abstract : The potential contribution of inflammation to the development of neuropsychiatric diseases has recently received substantial attention. In the brain, the main immune cells are the microglia. As they are the main source of inflammatory factors, it is plausible that the regulation of their activation may be a potential therapeutic target. Fractalkine (CX3CL1) and its receptor CX3CR1 play a crucial role in the control of the biological activity of the microglia. In the present study, using microglial cultures we investigated whether fractalkine is able to reverse changes in microglia caused by a prenatal stress procedure. Our study found that the microglia do not express fractalkine. Prenatal stress decreases the expression of the fractalkine receptor, which in turn is enhanced by the administration of exogenous fractalkine. Moreover, treatment with fractalkine diminishes the prenatal stress-induced overproduction of proinflammatory factors such as IL-1 β, IL-18, IL-6, TNF- α, CCL2, or NO in the microglial cells derived from prenatally stressed newborns. In conclusion, the present results revealed that the pathological activation of microglia in prenatally stressed newborns may be attenuated by fractalkine administration. Therefore, understanding of the role of the CX3CL1-CX3CR1 system may help to elucidate the mechanisms underlying the neuron-microglia interaction and its role in pathological conditions in the brain.